Analisis Penerapan dan Efektivitas Pendekatan Komunikatif dan Gramatika-Terjemah dalam Pembelajaran Bahasa Arab - Rizqi Maulana; Elsy Yulia Rahmani; Nur Hidayatul Wakhidah; M. Yunus Abu Bakar (Kampus Akademik Publiser, 2026)
Abstract. This study aims to analyze the implementation and effectiveness of the communicative and grammar-translation approaches in Arabic language learning. This research is motivated by the different orientations of the two approaches in developing students’ language skills. The communicative approach emphasizes using language in real-world communication, while the grammar-translation approach focuses more on mastering grammatical rules and translating texts. This study employed a library research method with a qualitative descriptive approach. The data were obtained from various literature sources, including books, scientific journals, and previous studies related to the communicative approach, grammar-translation approach, and Arabic language learning. Data collection techniques were carried out through documentation, while data analysis was conducted by identifying, classifying, comparing, and describing data relevant to the research focus. The results of the study indicate that the communicative approach is more effective in developing speaking (kalām) and listening (istimā’) skills because the learning process is oriented toward communication practices through dialogues, discussions, simulations, and other communicative activities. This approach also encourages students’ active participation in the learning process. Meanwhile, the grammar-translation approach is more effective in developing reading (qirā’ah) and writing (kitābah) skills, especially in understanding academic and religious Arabic texts through grammatical analysis and translation activities. Based on the findings, it can be concluded that both approaches have their own strengths and limitations. Therefore, the balanced and complementary use of both approaches is considered more effective in supporting the comprehensive development of Arabic language skills.